Comparative study between traffic control methods Using simulation software - Taha Alshaikhli , Imad Fakhri; Alkandari, Abdulrahman; Najaa, Anas (IACSIT Press, 2013)

(untitled)
Traffic jams are a huge issue in urban streets. Intersections are one of the critical parts of the street that causes high amount of congestion if not managed properly. Solutions where made that revolve around fixed set of operations that attempt to find optimum time for each traffic light in the intersection. Several solutions were proposed over the last years that use a more intelligent and more dynamic than the previous ones. Some of those approaches, labeled as Intelligent Traffic Light Control System, are discussed in this paper. The methods are Webster, Dynamic Webster, Equal Interval and Optimum Equal. A simulation software will run those methods in a typical four-phase intersection and generate a report about their results. Each method is demonstrated and explained in the context of the simulation software. The methods are compared with emphasis on cycle interval time and flow rate. A conclusion is made about what can be improved in those methods.